In Conversation: LGBT+ Transitions Before and During Prison - Glazzard, Jonathan; Thomas, Scott (International Journal of Educational and Life Transitions, 2024)
Prison environments can be dangerous places in which hypermasculine discourses prevail. They are often dehumanising, inflexible and viewed as places of punishment rather than rehabilitation. Regimes of power circulate to reinforce informal hierarchies and violence, intimidation, physical and sexual abuse may go unchallenged. Within this context, LGBT+ people in prison are particularly vulnerable. This paper uses extracts of dialogue from conversations which took place between both authors between March-April 2024. We focused our dialogue on educational and life transitions before and during prison to capture the lived experiences of Scott, one of the authors of this paper. The dialogue highlights the multiple transitions which Scott has navigated before and during his time in prison. These transitions were synchronous, ongoing, and multi-dimensional. We do not offer a systematic analysis of the dialogues. Instead, we offer our individual reflective commentaries on the conversations and identify some implications for policy and practice. The insights from a serving prisoner and the application of Jindal-Snape’s Multiple and Multi-dimensional Transitions theory (Jindal-Snape, 2016) to this context provide a unique and original contribution to knowledge.